PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR DI SMPN 1 SENGKANG - Selviana, Yuli; Mustamin; Raehana, Syarifa; Bunyamin, Andi; Wahab, Abdul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study aims to determine the application of the Contextual Teaching and Learning (CTL) learning model, student learning outcomes, and the effect of the Contextual Teaching and Learning learning model on the learning outcomes of eighth-grade students in Islamic Religious Education at SMP Negeri 1 Sengkang, Wajo Regency. This study uses a quantitative approach with an associative research type. The study population was 233 eighth-grade students, while the research sample was 70 students determined using proportional random sampling techniques. Data collection techniques used were observation, questionnaires, and documentation. Data were analyzed using descriptive statistics and inferential statistics through the help of the SPSS program, which includes validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination (R²). The results of the study indicate that the application of the Contextual Teaching and Learning learning model in Islamic Religious Education subjects is in the moderate category. Student learning outcomes are also in the moderate category. The results of the regression test show that the Contextual Teaching and Learning learning model has a positive and significant effect on student learning outcomes, as evidenced by the calculated F value of 142.666 which is greater than the F table of 2.03 and the significance value of 0.000 which is smaller than 0.05. The coefficient of determination (R²) value of 0.898 indicates that 89.8% of the variation in student learning outcomes can be explained by the Contextual Teaching and Learning learning model variable, while the remaining 10.2% is influenced by other factors outside the study. Thus, the Contextual Teaching and Learning learning model is proven to be effective in improving student learning outcomes in the subject of Islamic Religious Education for class VIII at SMP Negeri 1 Sengkang, Wajo Regency.